Sex, age, and family structure influence dispersal away from social group after a forced migration - Kauppi, Jenni (My University, 2022)
Dispersal is movement of an individual away from its point of origin to a new social group or settlement habitat where it usually reproduces. In social species dispersal is not only moving from one environment to another but also shifting from one social group to another. Factors such as an individual’s sex and age, along with number of relatives and their presence in a habitat, might influence individual’s propensity to disperse. Their influence has been long studied in birds and mammals but only few behavioural ecology studies have focused on humans. Human studies that focus on the influence of individual characteristics affecting dispersal decisions are rare, and more research is needed to know how features such as sex, age, and family relations influence individual’s dispersal propensity. During the World War II people were evacuated from Karelia to new areas in western Finland; the evacuations were made in a way that individuals could live with others from the same Karelian municipality in the new areas as well, yet not everyone stayed in their designated area but left elsewhere. In this study I use a unique dataset of recorded movements and life histories of the evacuated Karelian population to test how individual characteristics such as sex, age, number of siblings, and being firstborn or laterborn, influence an individual’s dispersal away from their own social group. I only focused on farmers in the data to have a cohesive study group, and the individual’s birth municipality in Karelia functions as their social group. I found that young women dispersed more than young men and that the difference decreases with age, also firstborn individuals dispersed more than non-firstborns as the number of younger brothers grew. However, sisters did not have the same effect as brothers. The results suggest that young men might benefit more from staying and farming near a familiar social group, and therefore gather more resources, whereas young women could benefit more from moving elsewhere to find work or possibly spouses. The result also indicate that the increasing number of younger brothers might pressure firstborn individuals into moving elsewhere in order to lessen competition with or leave more resources to brothers. Sisters on the other hand, seem to have no influence on dispersal probability, possibly because they are less of a competition for resources. Overall, the results show that individual characteristics are important in understanding dispersal behaviour but environmental properties such as social structure might change the outcomes.
Keywords: dispersal, human study, sex, age, siblings, birth order, social group